Status halal of cosmestic poducts: an analysis of alcohol usage for selected skin toner products in Malaysia - Baharum, Nur Bahirah; Awang, Mohd Daud; Arshad, Syariena; Abd Gani, Siti Salwa; Abdullah, Amini Amir; Mustafa, Hasri; Ismail, Kamarulzaman (Human Resource Management Academic Research Society, 2021)
Alcohol is an organic solvent that is generally used in research and industry especially in food and beverage products. It is also widely used in cosmetic industries to produce cosmetic lines such as perfume, skin toner, and personal care products. However, the status of alcohol usage in skin toner from Syariah and scientific point of views are limited. Thus, the purpose of this study is to know the status of alcohol usage in skin toner products. This study regards the use of alcohol in cosmetic products and halal status of alcohol in branded cosmetic products in Malaysia. It also acknowledges the types of alcohol compound and the function of its safety to the consumer. The methodology of the study uses laboratory research to analyse data and obtain more regular and complete information. This study also uses a high-tech systematic tool, namely GC-MS. Gas chromatography-mass spectrometry (GC-MS) is utilised to identify alcohol substance in the cosmetic products. Results showed that ten alcohol compounds were identified in the sample facial skin toner products. These alcohols were 1,3-butanediol, 2- phenoxy ethanol, 1,2-pentanediol, octanol, ethanol, phenyl ethyl alcohol, benzyl alcohol, propanol, benzene methanol, and citronellol. These alcohols are used as cleaning agents and solvents in cosmetic products and are suitable to be applied to the skin. Among these ten alcohol compounds, three compounds were found with the highest percentages which were 2-phenoxy ethanol (92.75% ± 0.72%), benzyl alcohol (33.95% ± 7.12%) and 1,2-pentanediol (15.29% ± 6.59%). The results of this study demonstrate that the alcohol in cosmetics is produced by the scientific process and chemical reaction. The GC-MS device is considered to be the synthesis process. The results of the observations and interviews of the part researchers with science officials state that the alcohol compounds found in this study indicates the properties of this alcohol as a cleaning agent, a solvent on the outside only and safe for use. Furthermore, this study proves that the use of alcohol in skin toner products is permissible in Islam if the alcohol is derived from plants, fruits, and grains. In other word, the status of alcohol usage in skin toner products is permissible according to Syariah.